Symptoms of Selective Mutism in Non-clinical 3- to 6-Year-Old Children: Relations With Social Anxiety, Autistic Features, and Behavioral Inhibition - Muris, Peter; Monait, Nona; Weijsters, Lotte; Ollendick, Thomas H. (Frontiers in Psychology, 2021)
Selective mutism (SM) is a psychiatric condition that is characterized by a failure to speak in specific social situations (e.g., at school) despite speaking normally in other situations (e.g., at home). There is abundant evidence that anxiety, and social anxiety in particular, is a prominent feature of SM, which is the main reason why this condition is currently classified as an anxiety disorder. Meanwhile, there is increasing support for the notion that autism-related problems are also involved in SM. The present study examined the relations between SM and social anxiety, autistic features, and behavioral inhibition to the unfamiliar (i.e., the tendency to react with restraint and withdrawal when confronted with unfamiliar stimuli and situations). Parents of 172 3- to 6-year-old preschool children completed an online survey for measuring the relevant constructs. Results showed that there were positive and statistically significant correlations between SM and social anxiety, autistic features, and behavioral inhibition. Regression analyses revealed that (1) both social anxiety and autistic features accounted for a significant and unique proportion of the variance in SM scores, and (2) that both of these variables no longer made a significant contribution once behavioral inhibition was added to the model. It can be concluded that while the involvement of social anxiety is unambiguous in SM, autism-related problems are also implicated. Furthermore, behavioral inhibition seems to play a key role in the non-speaking behavior of non-clinical young children.